Handling test length bloat. (22nd April 2013) - Fraser, Gordon; Arcuri, Andrea
SUMMARY: The length of test cases is a little investigated topic in search‐based test generation for object‐oriented software, where test cases are sequences of method calls. Although intuitively longer tests can achieve higher overall code coverage, there is always the threat of bloat – a complex phenomenon in evolutionary computation, where the length abnormally grows over time. In this paper, we show that bloat indeed also occurs in the context of test generation for object‐oriented software. We present different techniques to overcome the problem of length bloat, and evaluate all possible combinations of these techniques using different starting lengths for the search. Experiments on a set of difficult search targets, selected from several open source and industrial projects, show that controlling bloat with the appropriate techniques can significantly improve the search performance. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Although intuitively longer tests can achieve higher code coverage, in search‐based testing, there is always the threat of bloat, that is, abnormal growth of test length. We present techniques to overcome the problem of length bloat and evaluate all possible combinations of these techniques using different starting lengths for the search. Experiments on a set of difficult search targets, selected from several open source and industrial projects, show that controlling bloat with the appropriate techniques can significantly improve the search performance.